Sign System Design as Information Media in Darussalam Islamic Education Institutions Surabaya - Fatihah Nahya Izayanah; Masnuna; Wiwik Dwi Susanti; Vandhu Hidayat; Hamam Asyhari (Future Science, 2022)
The Darussalam Islamic Education Institute has KB, PPT, TK, and TPA study groups. The building environment has not been equipped with a conducive environment, with a large number of study groups and the number of students making students feel less comfortable and safe. Every corner at LPI Darussalam can be used as a vehicle for learning for the development of children's basic abilities. LPI Darussalam requires a sign system as a medium for information on space instructions, space markers, and appeals to support the student learning process by using the pre-production stage including design strategies, communication strategies, creative strategies, and media strategies, the production stage includes visual concepts, and post-production stages include media implementation. With a sign system equipped with Darussalam students' illustrations and the use of bright colors and the selection of materials and sizes that are adapted to the students' space for playing and learning, it can be used as a vehicle in learning for the development of basic abilities for children's growth which includes aspects of language, cognitive, physical development. motor skills and art and students will feel safe and comfortable during the learning process at LPI Darussalam and teachers and students can interact optimally.